Effect of patient-delivered household contact tracing and prevention for tuberculosis: a household cluster-randomised trial in Malawi - Kaswaswa, K; MacPherson, P; Kumwenda, M; Mpunga, J; Thindwa, D; Nliwasa, M; Mwapasa, M; Odland, J; Tomoka, T; Chipungu, G; Mukaka, M; Corbett, EL (Public Library of Science, 2022)
Background Household contact tracing provides TB screening and TB preventive therapy (TPT) to contacts at high risk of TB disease. However, it is resource intensive, inconvenient, and often poorly implemented. We investigated a novel model aiming to improve uptake.